P‐117: FLI Structure for R1 Foldable AMOLED Display. Issue 1 (25th September 2020) - Xu, Chuan X.; Shu, Shi; Yao, Qi; Yuan, Guang C.; Wu, Hui L.; Sun, Shuang; Li, Zhao; Xue, Jin X.; Wang, Tie S.; Huang, Hai T.; Wang, Dong H.
Abstract : A 6.2inch WQHD+ R1 foldable AMOLED display with FLI structure having thin thickness, wide color gamut, high brightness and low reflectivity was obtained. FLI means a structure of RGB emitter, thin film encapsulation, On‐TFE‐Touch and low temperature color filter.